Extreme Male Brain Theory of Autism - Liu, Erin Y.; Konkle, Anne T.M. (Université d'Ottawa | University of Ottawa, 2011)
Autism spectrum conditions (ASCs) are a category of neurodevelopmental disorders with symptoms of communication and social impairment, and the exhibition of restrictive and repetitive behaviours. Their occurrence is greater in males than females and this sex difference has played an important part in hypothesizing their etiology. The Extreme Male Brain (EMB) theory is a cognitive model proposed by Simon Baron-Cohen to explain the aforementioned sex differences and potential cause of ASCs. It is based upon his Empathizing -Systemizing theory, which classifies individuals into one of five cognitive profiles (Type S, Type E, Type B, Extreme Type S and Extreme Type E). These cognitive profiles determine an individual’s ability to systemize and empa- thize. Systemizing is the ability to understand and derive the rules of a system, and requires deductive and analytical skills. Empathizing relates to understanding human emotion and behaviour, thus requires social and communication skills. Males tend to systemize better than empathize while females have an opposite profile. Based upon the EMB theory, autistic individuals would possess an Extreme Type S profile as their impairments in social communication can be explained by a deficit in empathizing, while their preoccupation with patterns and detail-oriented behaviour can be related to their high systemizing. Together, these cognitive models have resulted in the Foetal Testosterone (fT) Theory, which implicates high prenatal testosterone as a risk factor for the associated hypermasculinized cognitive profile of individuals with ASCs. This review paper assesses the validity of the EMB and fT theories by reviewing the literature relating fT with autistic traits in the general population. The seven studies confirmed a correlation between higher fT levels and an increase in autistic traits, but limitations need to be considered when generalizing this information to an ASC sample.
Keywords: autism spectrum disorders; extreme male brain theory; systemizing– empathizing theory; foetal testosterone theory